2017
DOI: 10.1002/jso.24507
|View full text |Cite
|
Sign up to set email alerts
|

Distal pancreatectomy for benign and low grade malignant tumors: Short‐term postoperative outcomes of spleen preservation—A systematic review and update meta‐analysis

Abstract: SPDP for benign and low grade malignant tumors is associated with shorter hospital stay and decreased morbidity compared to DPS. J. Surg. Oncol. 2017;115:137-143. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…However, as the role of the spleen has become better understood over the recent decades, SP-LDP has emerged as a first-choice operation for benign or low-grade malignant tumors located within the body or tail of the pancreas. Several studies showed higher complication rates after distal pancreatectomy with concomitant splenectomy [30][31][32]. In the present study, concomitant splenectomy was associated with more post-LDP complications.…”
Section: Discussionsupporting
confidence: 60%
“…However, as the role of the spleen has become better understood over the recent decades, SP-LDP has emerged as a first-choice operation for benign or low-grade malignant tumors located within the body or tail of the pancreas. Several studies showed higher complication rates after distal pancreatectomy with concomitant splenectomy [30][31][32]. In the present study, concomitant splenectomy was associated with more post-LDP complications.…”
Section: Discussionsupporting
confidence: 60%
“…DP can be performed with splenectomy or with splenic preservation. Several studies have suggested the feasibility and potential benefit of splenic preservation during DP including the preservation of immune function and reduction of the risk of overwhelming post-splenectomy infection, intraoperative blood loss, infections, and other complications related to the splenectomy procedure itself [14,20,21]. A splenic preserving technique has not been endorsed for pancreatic adenocarcinoma to avoid an inadequate oncologic operation [15].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment of benign and low-grade malignant tumors in the pancreatic body/tail always has the potential for spleen-preserving distal pancreatectomy (SPDP). SPDP is associated with lower rates of postoperative complications [8][9][10], such as thrombocytosis, embolism, and infection. Splenic vessel-sacrificing (Warshaw technique (WT)) SPDP and splenic vessel-preserving (Kimura technique (KT)) SPDP are two methods applied in SPDP [11,12].…”
Section: Introductionmentioning
confidence: 99%